How do Pregnant Women with Additional Health or Social Care Needs Experience Parenting Groups: Evidence from Delivery of Enhanced Triple P for Baby and Mellow Bumps as Part of the Trial of Healthy Relationships Initiatives in the Very Early Years (THRIVE). Issue 4 (2nd October 2022) - Buston, Katie; MacLachlan, Alice; Henderson, Marion
ABSTRACT: There is still relatively little known about when, why, how and in what circumstances parenting interventions are effective. Support within the group context has been theorised as a key mechanism. This paper explores how pregnant women with additional health or social care needs participating in two group parenting interventions—Mellow Bumps or Enhanced Triple P for Babies—experienced being in a parenting group, and how this shaped how they engaged with the interventions; and it examines how group delivery may have facilitated or inhibited the effectiveness of the interventions, and for whom it did so. Session evaluation forms ( n  = 708) and a post-intervention questionnaire ( n  = 117) were completed by participants. In-depth interviews were conducted following the MB/ETPB antenatal sessions ( n  = 19), and 6–12 months after the birth of their baby ( n  = 15). Group delivery of these parenting interventions had the potential to support participants, particularly those with multiple additional health and social care needs. There are, however, important caveats including patchy attendance reducing the supportiveness of the groups, and few discernible longer terms changes. More group sessions, less patchy attendance, and more encouragement from facilitators for the women to keep in touch, and to join other community parent–child groups after the birth of their baby are likely to have increased feelings of support and connectedness.